Serum IL-23, IL-17 and TNF-α level as Psoriasis severity markers: A hospital based cross sectional study. - Sultana, Sabia Shahin; Monir, Bayzid Bin; Bhowmik, Devolina; Mostafa, Hasbi Ara; Tarafder, Shirin; Nigar, Ismet; Asaduzzaman, T M (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: Psoriasis is an autoimmune chronic inflammatory disease where serum cytokines are marked as prime drivers of disease progression and severity. Objectives: To investigate serum TNF-α, IL-17 and IL-23 level according to disease severity of psoriasis. Methods: A total of 35 psoriasis patients and 35 healthy controls were enrolled. Disease severity of psoriatic patients was assessed by Psoriasis Area and Severity Index (PASI) scoring. Serum TNF-α, IL-17 and IL-23 of study subjects were measured by ELISA. Results: Serum level of is significantly increased in psoriasis patients than healthy controls. Among 35 patient 56.7% were suffering from moderate to severe psoriasis. Serum TNF-α level was more in mild group (P =0.70) and serum IL-23 level increased in moderate to severe psoriasis (P=0.42). Whereas serum IL-17 level significantly increased along with disease severity (P=0.03). Conclusion: Our study underscores the role of TNF-α, IL-17 and IL-23 in disease severity of psoriasis. J Shaheed Suhrawardy Med Coll 2022; 14(2): 25-29